RESEARCH ON THE ARCHITECTURAL RENEWAL OF HISTORIC BLOCKS IN CHINESE MODERN CITIES OF TOURISM, A CASE STUDY OF HANGZHOU CITY, CHINA - REN, SHI JIAN (ITB Journal Publisher, LPPM ITB, 2006)
From the viewpoints of urban architecture and culture, the cause of crises in modern tourism cities of China is analyzed and concluded as loss of urban cultural features. As a resolution, the status of historic blocks in those cities and their influence on local tourism are explored. Harmonization between the renewal and succession of historic blocks contributes to improving local residential environment and attracting more tourists. Based on the practice of theprotection project of Qing-He-Fang Street in Hangzhou, China, the architectural methodology and the technologic measures in historic block protection are discussed. The results confirm that the renewal of historic blocks can resume local cultural tradition and inspire attraction to tourists.